Can anthropomorphic design in beverage packaging enhance impulse buying intention? Amazing visual and verbal cues! - Yuyang Tian; Siti Farhana Zakaria; Yinghui Du; Ye Qiu; Zenghui Tian (PLoS ONE, 2025)
The anthropomorphic design of beverage packaging has gained significant attention as an innovative marketing strategy. This study systematically examines how anthropomorphic visual and verbal cues in beverage packaging influence consumers’ impulse buying intentions. Grounded in the Stimulus-Organism-Response model, Social Presence Theory, and Empathy Theory, the research employs a consumer survey to validate the mediating roles of positive emotions, social presence, and empathy in the relationship between anthropomorphic design and impulse buying intentions. A comprehensive causal model was developed to explore these relationships. While modern packaging techniques and visual elements enhance the appearance of beverage packaging, they did not significantly trigger empathetic responses. This suggests that emotional language and personalized expressions are more effective in fostering emotional resonance. The study also highlights the significant mediating roles of positive emotions and social presence in the relationship between anthropomorphic design and impulse buying intentions, emphasizing the importance of emotional and social factors in consumer decision-making.This research validates the theoretical model and offers practical insights for companies. It suggests that businesses should focus on consumers’ emotional needs and psychological states in packaging design and marketing strategies. By enhancing emotional language, optimizing visual anthropomorphic elements, and incorporating multi-sensory designs, companies can effectively improve consumers’ positive emotions and social presence, thereby increasing impulse buying intentions. For consumers with high levels of loneliness, strengthening anthropomorphic design elements can meet their social and emotional needs, enhancing brand loyalty and market competitiveness.